Fluorescent Antibiotics: New Research Tools to Fight Antibiotic Resistance. Issue 5 (May 2018) - Stone, M. Rhia L.; Butler, Mark S.; Phetsang, Wanida; Cooper, Matthew A.; Blaskovich, Mark A.T.
Abstract : Better understanding how multidrug-resistant (MDR) bacteria can evade current and novel antibiotics requires a better understanding of the chemical biology of antibiotic action. This necessitates using new tools and techniques to advance our knowledge of bacterial responses to antibiotics, ideally in live cells in real time, to selectively investigate bacterial growth, division, metabolism, and resistance in response to antibiotic challenge. In this review, we discuss the preparation and biological evaluation of fluorescent antibiotics, focussing on how these reporters and assay methods can help elucidate resistance mechanisms. We also examine the potential utility of such probes for real-time in vivo diagnosis of infections. Highlights: Antimicrobial resistance (AMR) is a global health threat of increasing concern, predicted to result in a 'post-antibiotic' era with ten million deaths per year by 2050 if new approaches are not developed. More research is needed into the discovery and development of new antibiotics to effectively treat infections. Just as importantly, we need new diagnostics that can rapidly identify bacterial infections, allowing for moretimely and appropriate therapy. Fluorescent derivatives of antibiotics have great potential to be applied to AMR research, from improving our basic understanding of antibiotic modes of action to the development of non-invasive imaging for clinical diagnostics.